Travellers and immigrants fans of Wagner as cultural mediators between Germany and Argentina: translations, books and magazines at the beginning of the 20th century - Irurzun, María Josefina (Meridional. Revista Chilena de Estudios Latinoamericanos, 2024)
In this article we address the ways in which the "musical journey" to Europe made possible the transit and formation of knowledge between Argentina and Germany, from the physical support of the book "in movement" as well as the practices related to printed culture and translation, in Buenos Aires at the beginning of the twentieth century. Three different modalities of circulation and reading of printed books on Wagner’s work, enabled by the trip to Bayreuth, the Mecca of the "Wagnerian cult", are compared in an exploratory way. Firstly, we consider the personal narrative within the style tradition of the tourist guides in circulation during the 19th century, with the case of Miguel Cané (Jr.). Secondly, the impact of first-hand access to the complete works of the German philosopher Friedrich Nietzsche by the music critic Mariano Barrenechea in the pre- and post-World War I period. Finally, the interpretative work carried out by Josep Lleonart Nart - a leader of the Catalan immigrant community in Buenos Aires - as a member of a transnational group of Catalan critics and enthusiasts whose journey to the "green hill" had served as an input to translate the dramatic aspect of Wagnerian art.